A network control system for hydro plants to counteract the non-synchronous generation integration. (February 2019) - Chamorro, Harold R.; Sanchez, Andres C.; Pantoja, Andres; Zelinka, Ivan; Gonzalez-Longatt, Francisco; Sood, Vijay K.
Highlights: The addition of a supplementary derivative control to the hydro-governors through a network control system and its distributive control action obtained by the application of an evolutionary game theory, the replicator dynamics. The proper tuning of the control parameters that guarantee an optimal response in the frequency control application. The combination of two powerful methods to improve the primary frequency control to mitigate the integration of the renewables into the grid. The application of the methods in two systems, an aggregated model and a large power system. Abstract: Sweden, a country with abundant hydro power, has expectations to include more wind power into its electrical system. Currently, in order to improve the frequency response requirements of its electrical system, the country is considering upgrading its hydro-governors. This effort is part of maintaining the system frequency and reaction within their limits following any disturbance events. To partially compensate for increased frequency fluctuations due to an increased share of renewables on its system, the frequency response of hydro-governors should be improved. This paper proposes an innovative network control system, through a supplementary control, for the improvement of the hydro-governor's action. This supplementary control allows having more flexibility over the control action and improves the primary frequency control, and thereby the overall system frequency response. The proposed supplementary control, based on an evolutionary game theory strategy, uses remote measurements and a hierarchical dynamic adjustment of the control. Additionally, in order to guarantee an optimal response, a Simulated Annealing Algorithm (SAA) is combined with the supplementary control. This paper illustrates the analysis and design of the proposed methodology, and is tested on two power systems models: (i) an aggregated model that represents the frequency response of Sweden, Norway and Finland, and (ii) The Nordic 32 test system.